Marriage across cultures and its implications to the church: A survey of Christ is the answer Ministries, Kenya - Kibuthu, Isaac (PAC University journal of arts and social sciences, 2016)
Marriage across cultures is not fully accepted by many ethnic groups, even among those who have embraced Christianity. The research on which this paper is based investigated the trends of Christian marriages across cultures in terms of numbers, age at marriage, motivation and ethnic groups involved. The study employed both qualitative and quantitative design methods in data collection and analysis. The population comprised seven assemblies of Christ Is The Answer Ministries. The sample consisted of 247 respondents in marriage across cultures, seven senior pastors, seven pastors’ in-charge of Family Care and Enrichment Ministry and three couples in a focus group discussion. The main data collection tool was a questionnaire. Data were analysed using the Statistical Package for the Social Sciences (SPSS). The study found that marriages across cultures are on the increase, the age at marriage for both men and women is increasing but the age difference is decreasing. Love for one another and a common faith in Christ were found to be the main motivations to marriage. The ethnic groups leading in marriage across cultures among men are Luo, Luhya, Kikuyu and Kamba while among women are Kikuyu, Luhya, Kamba and Kalenjin. The study recommends an improvement on keeping of marriage records and members’ contacts; creation of awareness among youth and parents on marriage across cultures as a way of preparing them for such unions and dealing with ethnic prejudice/stereotypes to enhance acceptability. It is further recommended that the Church address issues of ethnicity and marriage across cultures as part of its pulpit ministry.
Keywords: Cross cultural marriage; Church; CITAM; christian marriages